If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(r + 5) = 4r Reorder the terms: 2(5 + r) = 4r (5 * 2 + r * 2) = 4r (10 + 2r) = 4r Solving 10 + 2r = 4r Solving for variable 'r'. Move all terms containing r to the left, all other terms to the right. Add '-4r' to each side of the equation. 10 + 2r + -4r = 4r + -4r Combine like terms: 2r + -4r = -2r 10 + -2r = 4r + -4r Combine like terms: 4r + -4r = 0 10 + -2r = 0 Add '-10' to each side of the equation. 10 + -10 + -2r = 0 + -10 Combine like terms: 10 + -10 = 0 0 + -2r = 0 + -10 -2r = 0 + -10 Combine like terms: 0 + -10 = -10 -2r = -10 Divide each side by '-2'. r = 5 Simplifying r = 5
| (10x-1)+(5x+6)= | | 275=60x+25(4) | | 9x^4+16x^3-76x^2-8x+32=0 | | 3(b+2)=2(c+3) | | 14x+12y=178 | | 3(c-2)=(c+3) | | 6x^2y-2xy^2+3xy-5= | | 4x^2+3y^2-16x+12y+16=0 | | -x^3+6x^2-11x+6=0 | | -5x+27=3y | | n=4.7 | | sqrt(8x+1)+sqrt(3x-5)=sqrt(7x+4)+sqrt(2x-2) | | x=16+-9(2) | | 3x+2y=7whatisx | | 6x-8=20x-22 | | 3(16+-9y)+8y=10 | | (5b-5d)(5b+4d)= | | (4x^2)+(3y^2)-16x+12y+16=0 | | x=16+-9(1) | | x+2y+2z-5=0 | | 7+3(2+x)=28 | | 5y+3y^2=2 | | x^2+2x=y^2 | | (3xy+2z)(2xy-3z)= | | 6(3+-9y)+8y=-28 | | x^3-y^3+216=18y(-x) | | 3x^2+30x-17=-122 | | -14=4z | | log(2x-10)-log(10)=1 | | 10xy^2=0 | | 9xn=-27 | | -5+2x^2=-5x |